(untitled) (Fiep Bulletin - online, 2019)
The improvement of the components of Physical Fitness enables children and adolescents to identify thesecomponents and their health benefits, seeking to stimulate the development of a physically active lifestyle until the age ofmajority. The objective of the present study was to identify the physical fitness levels of elementary school students from thepublic and private schools of the city of São José do Egito in Pernambuco. The research had a cross-sectional descriptive designof ex post fact typology, the randomized sample was composed of three hundred students of both sexes. The data wereprocessed and analyzed with the aid of SPSS 20. The statistical analysis was of the inferential type. Applied statistical treatments:ANOVA variance analysis test, to observe the difference between variables was used the Tukey Post Hoc test. Pearson’s testwas used to determine the levels of correlation between the variables. The results presented by means of the measures ofminimum, maximum and average central tendency and the dispersion measures (standard deviation - SD), adopting ? = 5% forthe acceptance of the statistically significant differences. The results regarding age did not present a significant difference,presenting significant differences regarding flexibility, localized muscular endurance and cardiorespiratory resistance, notcorroborated by Tukey Post Hoc test. It was concluded that more detailed studies are done in relation to the topic addressed andpromotion physical activity and healthy eating at school, as a way to prevent overweight and obesity.